Problematising the role of Community Arts Centres: examining and analysing the role of Community Arts Centres in South African Townships - Ngwenya, Smangaliso Siphesihle (My University, 2021)
Common, communicate, communal and community possess at their essence a shared or a sharing experience. Community arts centres are meant to be spaces which catalyse and embody a sharing space for arts and culture. However, there is a widening disconnect between community arts centres and their respective surrounding communities within South African townships. An eMalahleni township-based arts centre, Izodela Community Development Centre as a case study, provides an in-depth, layered opportunity to delve into examining and analysing this disconnect. This analysis and examination unearth the roots of the growing disconnect embedded in lack of participation and communication in the centre-community relationship regarding programming, the creation of cultural goods and services, management, governance as well as issues embedded in infrastructural deficiencies. The study also provides room for a comprehensive and thorough exploration of prospective solutions namely co-authorship, cultural democracy and community cultural development. These three are proposed as agents to mitigate and eventually remove the disconnect that exists between community arts centres and their surrounding communities in South African townships. It is through acknowledging and digging into the roots of the disconnect that exists in the centre-community relationship that solutions entrenched in co-authorship and cultural democracy can be used to rectify it and, in turn, transform community arts centres into community cultural development centres
A thesis submitted to Faculty of Humanities, University of the Witwatersrand in partial fulfilment of requirements of the degree of Master of Arts (by Coursework) in the field of in the field of Cultural Policy and Management, 2021